Analysis of Dynamic Vibration Characteristics in Daihatsu Taft Hiline Gtl Transmission with Fea - Harris Kristanto (Trigin Publisher, 2021)
Transmission is function to move and to change the power from motor, which is used to turn machine spindle as well as to do feeding movement. The vibration level which occurred in transmission is very important so that a failure does not occur. The purpose of this research is to know vibration phenomenon and vibration mode which occurred to transmission. Material and boundary condition which is used influenced natural frequency and occurred vibration mode. Method which will be used in this vibration analysis is by using modal analysis based on FEA. Software is used in building the CAD shape and FEA process. Numeric model characterized stiffness structure matrix is built to investigate transmission vibration. The results obtained in this research is the natural frequency of neutral gear (1,109.1–1,780.2) Hz, 1st gear (1,173.2–1,795.6) Hz, 2nd gear (1,107.8-1,804.4) Hz, 3th gear (1,206.2–1,805.3) Hz, 4th gear (1,156.3 to 1,804.5) Hz, 5th gear (1,099.3–1,738) Hz, and reverse gear (1,171.6–1,870) Hz. In this research resulted that the smallest natural frequency occurred at the first mode 5th gear is 1,099.3 Hz, While the biggest natural frequency occurred at the eighth mode reverse gear is 1,870 Hz. This matter because contact relation which occured at 5th gear is minim so that the mass of the gear is lighter, while at the reverse gear thas three related wheel gears so that the masses are heavier and produce natural frequencies greater.